2006
DOI: 10.1152/jn.01256.2005
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Encoding of Frequency and Amplitude Modulation in Human Auditory Cortex: MEG Evidence

Abstract: Luo H, Wang Y, Poeppel D, Simon JZ. Concurrent encoding of frequency and amplitude modulation in human auditory cortex: encoding transition. J Neurophysiol 98: 3473-3485, 2007. First published September 26, 2007 doi:10.1152/jn.00342.2007. Complex natural sounds (e.g., animal vocalizations or speech) can be characterized by specific spectrotemporal patterns the components of which change in both frequency (FM) and amplitude (AM). The neural coding of AM and FM has been widely studied in humans and animals but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 67 publications
2
56
2
Order By: Relevance
“…Moreover, although phase locking to FM stimuli has been observed (27)(28)(29), this study shows optimal-phase effects due to phase locking to an auditory stimulus modulated only spectrally (i.e., without any rhythmic amplitude fluctuations). Thus, the current results are suggestive that spectral fluctuations in natural auditory stimuli may act as a pacing signal for low-frequency oscillations and may, in turn, influence auditory perception.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, although phase locking to FM stimuli has been observed (27)(28)(29), this study shows optimal-phase effects due to phase locking to an auditory stimulus modulated only spectrally (i.e., without any rhythmic amplitude fluctuations). Thus, the current results are suggestive that spectral fluctuations in natural auditory stimuli may act as a pacing signal for low-frequency oscillations and may, in turn, influence auditory perception.…”
Section: Discussionmentioning
confidence: 53%
“…As such, the current study made use of simple nonspeech auditory stimuli, where periodicity was communicated by frequency modulation (FM) rather than amplitude fluctuations (i.e., onsets). Although neural oscillations have been shown to be entrained by FM (27)(28)(29), the possibility that slow FM provides a pacing signal for phase alignment has not received much scientific attention (29).…”
mentioning
confidence: 99%
“…Notably, however, we did not observe a 5.075-Hz peak in the analysis of AM-aligned brain signals. The reason for this is that human auditory cortex relies on a phase-coding mechanism to efficiently code complex rhythmic signals containing simultaneous AM and FM (38)(39)(40); critically, the instantaneous phase of the entrained neural oscillation with respect to the AM codes for the instantaneous frequency of the FM.…”
Section: Neural Entrainment By Complex Rhythmic Stimuli Comodulatesmentioning
confidence: 99%
“…Temporal modulations describe the changes in an audio signal in terms of amplitude modulation (AM) and frequency modulation (FM) [22]. It is observed that AM and FM always co-occur and are inseparable features of the audio signal [22]. AM-FM responses can be obtained from the filterbank model of the cochlea.…”
Section: B Teager Energy Operator (Teo)mentioning
confidence: 99%
“…The cepstral coefficients extracted using Gammatone filterbank have been previously used for speech recognition [18]- [20], and non-speech audio classification [21]. Unlike conventional energy (l 2 -norm), Teager Energy Operator (TEO) profile represents both amplitude and frequency variations of a signal [22]. In experiments, we used cepstral features, and spectral features for two classifiers, namely, GMM, and CNN, respectively.…”
Section: Introductionmentioning
confidence: 99%